Structure – properties relationships of graphene and spinel nickel ferrites based poly(vinylidene fluoride) hybrid polymer nanocomposites for improved dielectric and EMI shielding characteristics. (April 2022) - Ahmed, Ibrar; Khan, Ahmad Nawaz; Jan, Rahim; Gul, Iftikhar Hussain
Highlights: The structure-properties correlation of neat PVDF is tailored by the addition of graphene and spinel nickel ferrites (nFE) nanoparticles. PVDF/graphene nanocomposites exhibited synergistic balance in the improvement of thermal, mechanical, dielectric and EMI shielding behaviors. PVDF/graphene/nFE hybrid nanocomposites lacks the synergistic balance in the enhancement of the properties as EMI shielding performance remarkably improved at the expense of stiffness, toughness and ductility. Abstract: Hybrid polymer nanocomposites with poly(vinylidene fluoride) are prepared based on graphene and spinel nickel ferrites (nFE) nanoparticles to investigate their structure-properties relationships. X-ray diffraction and differential scanning calorimetry confirmed the co-existence of α- and β-crystal phases of PVDF by the incorporation of graphene and nFE whereas solely α- crystal phase formed in neat PVDF. The influence of graphene and nFE on the mechanical properties of PVDF is concentration dependant. The modulus of PVDF is enhanced ∼ 128% from 587 to 1340 MPa at the expense of reduction in failure strain from 18% to 6% in PVDF/graphene nanocomposite whereas in PVDF/graphene/nFE hybrid nanocomposites, the mechanical properties are reduced owing to the embrittlement. On the contrary, graphene-nFE-polymer interfacial space charge accumulation has caused the enhancement of dielectric and EMI shielding characteristics as a function of frequency (1kHz-5 MHz). In PVDF/graphene nanocomposites at 3 wt%, the dielectric constant (ε / ) value is increased 16-fold while keeping the dielectric loss (ε // ) values equivalent to neat PVDF. Whereas, both ε / and ε // are increased enormously in PVDF/graphene/nFE hybrid nanocomposites along the whole frequency range. Similarly, EMI shielding (SET ) of PVDF/graphene and PVDF/graphene/nFE is ∼ 16 and 22 dB, respectively for a film thickness of ∼0.2 mm. Comparatively, PVDF/graphene nanocomposites exhibited the synergistic balance in mechanical, dielectric and EMI shielding properties over PVDF/graphene/nFE hybrid nanocomposites. Graphical abstract: Image, graphical abstract